Diagnosis of Lumbosacral Radiculopathy: MRI vs NCS - Parui, Sandip Kumar (Current Progress in Medicine and Medical Research Vol. 5, 2023)
This chapter evaluate the potential of soleus H-reflex for diagnosis of radiculopathies along with its comparison with imaging (MRI) and clinical examination. Since Mixter & Barr initially described lumbrosacral radiculopathy in 1934, it has become one of the most prevalent causes of low back pain. In the current study, we assessed and contrasted the value of MRI of the lumbosacral spine and Soleus H-Reflex study for the diagnosis of lumbosacral radiculopathy. An observational cross-sectional study was performed on 20 patients (11 females & 9 males) clinically diagnosed as lumbosacral radiculopathy at orthopaedic OPD of R. G. Kar Medical College, Kolkata. Soleus H-Reflex study was performed first and then they had undergone MRI of L-S spine. All collected data were analyzed by SPSS programme. There may be noncompressive causes of radiculopathy which include ischemia, trauma, neoplastic infiltration, spinal infections, postradiation injury, immune-mediated diseases; these present with electrodiagnostic patterns indistinguishable from nerve root compression. 55% patients showed radiculopathy in their MRI while H-Reflex was abnormal in 80% patients. Out of these 80%, 40% showed unilateral absence, 35% bilateral absence and 5% decreased H amplitude. There was significant correlation between MRI and H-reflex study with a p value of 0.013. According to kappa coefficient assessment there was moderate strength of agreement between these two tests (Kappa-0.468). An interesting finding was that 5 patients out of 9 who had normal MRI; had abnormal H-Reflex result (55.56%). The study can be concluded that H-reflex is an efficient diagnostic tool for lumbosacral radiculopathy as evidenced by 80% abnormal result, whereas MRI showed 55% positive results. It is a useful diagnostic tool since individuals with L-S Radiculopathy exhibit an aberrant H-Reflex in 80% of cases. More than 55% of patients with clinically diagnosed radiculopathy who also have normal MRIs leave plenty of potential for further investigation into whether functional change can happen earlier than structural anomalies seen on MRI.